2016
DOI: 10.1037/pas0000153
|View full text |Cite
|
Sign up to set email alerts
|

Higher- and lower-order factor analyses of the Children’s Behavior Questionnaire in early and middle childhood.

Abstract: The Children’s Behavior Questionnaire (CBQ; Rothbart, Ahadi, & Hershey, 1994), a 195-item parent-report questionnaire, is one of the most widely used measures of child temperament, with previous analyses of its scales suggesting that three broad factors account for the overarching structure of child temperament (Rothbart, Ahadi, Hersey, & Fisher, 2001). However, there are no published item-level factor analyses of the CBQ, meaning that it is currently unclear whether items clearly load onto CBQ scales as propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 50 publications
2
33
0
1
Order By: Relevance
“…These item-level results are not surprising. A previous study from our group (Kotelnikova et al, 2016) showed that less than half of the original 195 CBQ items loaded onto lower-order scales. The TMCQ was developed via a top-down approach as an adaptation of the CBQ for older children, and approximately a third of the TMCQ items were taken verbatim from the CBQ.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These item-level results are not surprising. A previous study from our group (Kotelnikova et al, 2016) showed that less than half of the original 195 CBQ items loaded onto lower-order scales. The TMCQ was developed via a top-down approach as an adaptation of the CBQ for older children, and approximately a third of the TMCQ items were taken verbatim from the CBQ.…”
Section: Discussionmentioning
confidence: 83%
“…The fourth factor, labeled Sociability/Affiliation, combines Agreeableness and Openness to Experience. In the study of the CBQ previously mentioned (Kotelnikova et al, 2016), higher-order factor analyses yielded a model that showed only minimal resemblance to that proposed by Rothbart and colleagues (2001); in particular, while NA-like and Extraversion/Surgency-like factors were found, no clear EC factor was recovered (Kotelnikova et al, 2016). Given the item overlap between the TMCQ and CBQ noted earlier, and the lack of extensive factor-analytic work on the TMCQ, further analyses of its higher-order structure are clearly needed.…”
mentioning
confidence: 98%
“…Kotelnikova et al, 2015). Typically, the Effortful Control dimension includes the facets of attentional focusing, inhibitory control, low intensity pleasure, and perceptual sensitivity (Rothbart et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, across developmental periods and specific instruments, there are several key constructs assessed that are directly applicable to and fill the gaps that are left by other measures in assessing the PVS. Finally, although original Rothbart scales are described below, there may be alternative formulations of the items that better explain those data (Kotelnikova, Olino, Klein, Krysti, & Hayden, in press). However, these also may be useful for understanding PVS function.…”
Section: Developmental Extensions Of Pvsmentioning
confidence: 99%